2021
DOI: 10.19109/alkimia.v4i2.7333
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Extraction of Nothaphoebe Coriacea Bark and Its Antioxidant Evaluation

Abstract: Nothaphoebe coriacea (in Kalimantan, Indonesia, commonly known as gemor) is a native wetland-plants that can grow well in swampy areas. This tree is distributed throughout South and Central Kalimantan, Indonesia. The bark of Nothaphoebe coriacea is used for bioactive compound source for larvacide, mosquito repellent, hio and glue. The objective of this research was to investigate the ultrasound-assisted extraction methods for the extraction of antioxidants compounds of Nothaphoebe coriacea. The barks were subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…With the extension of extraction time, the extraction efficiency of lutein between different methods also represented an increasing trend (Figure 1b ). Sonication is an effective tool for extracting organics, it requires simple equipment, and liquid–solid separations can usually be achieved in a short time (Sunardi & Nisa, 2021 ). Compared with the two methods, microwave‐assisted extraction was time‐saving and more efficient, which has a certain auxiliary effect on lutein extraction in terms of extraction time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the extension of extraction time, the extraction efficiency of lutein between different methods also represented an increasing trend (Figure 1b ). Sonication is an effective tool for extracting organics, it requires simple equipment, and liquid–solid separations can usually be achieved in a short time (Sunardi & Nisa, 2021 ). Compared with the two methods, microwave‐assisted extraction was time‐saving and more efficient, which has a certain auxiliary effect on lutein extraction in terms of extraction time.…”
Section: Resultsmentioning
confidence: 99%
“…of lutein between different methods also represented an increasing trend (Figure 1b). Sonication is an effective tool for extracting organics, it requires simple equipment, and liquid-solid separations can usually be achieved in a short time (Sunardi & Nisa, 2021). As shown in Figure 1c, the OD value of the two treatments showed an increasing trend in the process of the solid-liquid ratio increasing, which indicated that lutein was in full contact with ethanol in the beginning and had been completely exact.…”
Section: With the Extension Of Extraction Time The Extraction Efficiencymentioning
confidence: 95%